2008
DOI: 10.1080/00365520701580066
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to assess gastric accommodation and peristaltic motility in conscious rats

Abstract: We conclude that IGP measurement during test-meal infusion represents an efficient and novel method to compare gastric accommodation and peristaltic motility in the whole stomach of conscious rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 31 publications
5
28
1
Order By: Relevance
“…This increase was followed by a plateau phase during which IGP hardly increased despite further nutrient infusion. These findings correspond to results from previous experiments in which the same animal model was used (15). It was suggested that the plateau phase, during which IGP is stable but intragastric nutrient infusion continues, represents a reflex gastric relaxation upon food ingestion and thus GA.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This increase was followed by a plateau phase during which IGP hardly increased despite further nutrient infusion. These findings correspond to results from previous experiments in which the same animal model was used (15). It was suggested that the plateau phase, during which IGP is stable but intragastric nutrient infusion continues, represents a reflex gastric relaxation upon food ingestion and thus GA.…”
Section: Discussionsupporting
confidence: 77%
“…The experimental protocol was similar to that used in Janssen et al (15). Animals were fasted overnight before the beginning of each experiment to prevent the presence of food particles in the stomach, and access to water was provided ad libitum.…”
Section: Ga Studymentioning
confidence: 99%
See 2 more Smart Citations
“…This finding shows that the adaptive relaxation of the stomach is induced through the generation of NO. Janssen et al (2008Janssen et al ( , 2010 showed that L-NAME significantly increased intragastric pressure during stomach distension, indicating decreased gastric accommodation. These reports are in accord with our present result with L-NAME.…”
Section: Discussionmentioning
confidence: 99%